Tailored Synthesis of 162‐Residue S‐Monoglycosylated GM2‐Activator Protein (GM2AP) Analogues that Allows Facile Access to a Protein Library. (19th August 2016) - Nakamura, Takahiro; Sato, Kohei; Naruse, Naoto; Kitakaze, Keisuke; Inokuma, Tsubasa; Hirokawa, Takatsugu; Shigenaga, Akira; Itoh, Kohji; Otaka, Akira
Abstract: A synthetic protocol for the preparation of 162‐residue S ‐monoglycosylated GM2‐activator protein (GM2AP) analogues bearing various amino acid substitutions for Thr69 has been developed. The facile incorporation of the replacements into the protein was achieved by means of a one‐pot/N‐to‐C‐directed sequential ligation strategy using readily accessible middle N ‐sulfanylethylanilide (SEAlide) peptides each consisting of seven amino acid residues. A kinetically controlled ligation protocol was successfully applied to the assembly of three peptide segments covering the GM2AP. The native chemical ligation (NCL) reactivities of the SEAlide peptides can be tuned by the presence or absence of phosphate salts. Furthermore, NCL of the alkyl thioester fragment [GM2AP (1–31)] with the N‐terminal cysteinyl prolyl thioester [GM2AP (32–67)] proceeded smoothly to yield the 67‐residue prolyl thioester, with the prolyl thioester moiety remaining intact. This newly developed strategy enabled the facile synthesis of GM2AP analogues. Thus, we refer to this synthetic protocol as "tailored synthesis" for the construction of a GM2AP library. Abstract : Fine‐tuning peptide ligation : A protocol for the preparation of 162‐residue S‐monoglycosylated GM2‐activator protein analogues containing various single‐amino‐acid substitutions for Thr69 has been developed. The facile incorporation of these replacements into the whole protein was achieved through a sequential ligation strategy using readily accessible short middle N ‐sulfanylethylanilide peptide segments.